Breast feeding, Islamic guidance and scientific evidence - Rahman, Md. Mokhlesur; Akter, Seikh Farid Uddin (Centre for Promoting Ideas, USA, 2011)
Breast feeding by the mother to her new born infant is greatly beneficial. It is prescribed as Almighty commanded the mother to breast feed her child for two years: "The mothers shall give such to their offspring for two whole years” if the father desires to complete the term. But he shall bear the cost of their food and clothing on equal length of period accordingly. If they both decide on weaning, by mutual understanding after due consultation, there is no blame on them. Directives also appear in the Noble Quran: If ye decide on a foster-mother for your offspring, there is no blame on you, provided ye pay (the mother) what ye offered, on equitable terms. But fear God and know that God sees well what ye do. (The Noble Quran, 2:233)"